The Influence Between Social Capital and Technology Use in Increasing the Competitiveness of MSMEs in Bojonegoro District (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine the influence of social capital and technology use on increasing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Bojonegoro District. Using a quantitative survey-based approach, data were collected from 30 MSME respondents. The results of the analysis show that both social capital and technology use have a significant positive influence on MSME competitiveness. Social capital supports network development, information access, and collaboration, while digital technology improves operational efficiency and market reach. The synergy between these two factors provides a substantial competitive advantage. This study recommends training and strategic policies to improve both aspects to support MSME competitiveness.